Role of Various Stakeholders Towards Early Childhood Care and Development - Warbal, Anjali; Gogia, Nancy Gogia (THE PRIMARY TEACHER, 2018)
Children are an essential part of society. Early Childhood Care and Development (ECCD) plays a pivotal role in the holistic development of a child. It nourishes the child’s cognitive skills and helps them to adjust to their social environment in a better way. The family takes care of each and every aspect of a child’s life starting from birth until they grow up and become self-sustained. It acts as the first teacher to the child. Every child learns a lot from their family. The family develops cognitive, affective, and psychomotor skills in the child. The role of the family is also very important in the child’s academic performance. If the family provides a conducive environment for the child, then it will affect the development of the child. Society is that part of our life that we can never neglect. Through society, a child can learn many things; also, it can change their way of thinking. For the upliftment of the child, society plays a pivotal role. It creates a platform for the development of the child so that they become supportive, emotionally sound, intellectually strong, and physically healthy. Teachers are the epitome of God. They are the ones who, formally as well as informally, educate children. They are considered the guide, friends, and philosophers of the children. They are the motherly figure in the formative years of the children. They are filled with knowledge, attitude, behaviour and skills that are required to perform different tasks effectively. The present paper focuses on the role, problems and current issues that are faced by teachers, parents and society as a whole about ECCD. It explains the critical issues and challenges faced by various stakeholders. Furthermore, it also suggests some measures for further improvement.